Pelatihan Bantuan Hidup Dasar di Pesantren Mahasiswa Aqwamu Qila Tamanan Banguntapan Bantul - Ario Tejosukmono; Dewi Yuniasih; Moch. Junaidy Heriyanto; Muhammad Agita Hutomo; Annisa Annisa; Rachma Greta Perdana Putri (Universitas Pahlawan Tuanku Tambusai, 2023)
Basic life support (BHD) is an effort needed to save the lives of victims while waiting for professional help to arrive. Basic life support knowledge and skills are needed by all groups. Santri at the Aqwamu Qila Banguntapan student boarding school has never received exposure and training related to basic life support. This PKM activity aims to provide understanding and skills to students related to BHD. The PKM activity was held on Sunday, August 28 at the Aqwamu Qila Mosque, consisting of BHD counseling and training with presentations and BHD video screenings, and manikin simulations. After the presentation and video screening, the training participants were divided into 2 groups, male and female, to directly practice and simulate BHD on the manikin. The result of this training is that all participants understand and are more confident in doing BHD. By directly carrying out a simulation on a manikin, participants can immediately practice how to provide basic life assistance.